Ethnocultural Contacts of the Peoples of the Altai-Sayan and Western Mongolia - Sampildondov, Chuluun; Dongak, Antonina S. (The New Research of Tuva, 2015)
Ethnocultural Contacts of the Peoples of the Altai-Sayan and Western Mongolia
Keywords: Mongolia; TIGI; expedition; Sayano-Altai mountains; Western Mongolia; intercultural communication